THE ARTISTIC AND AESTHETIC CHARACTERISTICS OF BAXSHI CREATIVITY AND THE MASTER–APPRENTICE TRADITIONS IN MAQOM ART - Ashiraiyev Furqatjon Davron o‘g‘li (Western European Studies, 2025)
This article explores the artistic and aesthetic characteristics of the baxshi tradition in relation to the maqom art and their shared pedagogical system of the master–apprentice model. The study analyzes the deep interconnection between epic performance and classical maqom singing within the cultural context of the Third Renaissance in Uzbekistan. Drawing upon recent musicological research, the article highlights how the synthesis of baxshi oral poetry and maqom’s modal structure serves as a unique foundation for national music education and identity
Keywords: baxshi; maqom; oral tradition